EFFORTS TO CONTROL DENGUE VECTORS BY ERADICATING MOSQUITO NESTS AND PLANTING ZODIA PLANTS AS MOSQUITO REPELLENTS IN THE WORKING AREA OF THE SAKO HEALTH CENTER IN PALEMBANG CITY IN 2023 - Priyadi, Priyadi; Kamsul, Kamsul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The current mosquito nest eradication program (PSN) is not optimal, so alternative strategies are needed to overcome the problem. One of them is increasing efforts to eradicate dengue fever vectors, namely Ae. aegypti mosquitoes are the main vectors and Ae. Albopictus is the companion vector. Both types of mosquitoes are found throughout Indonesia, living optimally at altitudes above 1,000 m above sea level, but according to some reports can be found in areas with altitudes up to '1,500 m asl.m'. Aedes mosquitoes are native to Brazil and Ethiopia, and their adult stage is on average smaller than other types of mosquitoes. The efforts made are to socialize and cultivate zodiac plants as mosquito repellent, thus having an impact on reducing cases of dengue hemorrhagic fever (DHF) in the Sako Health Center area which continues to increase every year. The location of community service activities is the working area of the Sako Health Center where the incidence of dengue fever is quite high. Intended to serve the community, the methods used are by existing theories and research findings, namely Puskesmas, and officers in their target locations make efforts to plant/utilize zodiac plants to reduce the risk of disease cases—dengue hemorrhagic fever (DHF).